Twórca nowoczesnej chirurgii – Jan Mikulicz-Radecki i współcześni mu okuliści na Uniwersytecie Wrocławskim przełomu XIX i XX wieku - Niżankowska, Maria Hanna; Kalinowska, Joanna; Pacan, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The authors present the history of the life and achievements of Jan Mikulicz-Radecki as the creator of modern surgery and his own school of surgery, especially during his work at the Wroclaw University in 1890 – 1905 years. The contemporary ophthalmologists as Richard Foerster, Hermann Ludwig Cohn, Wilhelm Uhthoff and theirs famous coworkers are also presented.